Lower-Third SLOE Rankings Impede, But Do Not Prevent, A Match in Emergency Medicine Residency Training. (December 2020) - Hansroth, Joseph A; Davis, Kristin H; Quedado, Kimberly D; Davis, Stephen M; Kiefer, Autumn S; Shaver, Erica B; Kiefer, Christopher S; Cottrell, Scott; Ferrari, Norman D
Objective: Emergency medicine program directors (PD) value the standardized letter of evaluation (SLOE) as the most important aspect of a residency application when making both invitation and ranking decisions. This study aims to determine whether the presence of any lower-third in either SLOE global assessment (GA) question impacted the ability of an applicant to match into EM. We hypothesized that any lower-third ranking would be associated with increased odds of not matching into EM. Methods: We conducted a retrospective cohort study evaluating allopathic applicants from medical schools in the United States (US allopathic applicants) to a single EM residency program during the 2018/2019 match cycles. GA SLOE rankings from all applications were tabulated and compared to the applicant's National Resident Matching Program (NRMP) match outcome. Comparative analyses were conducted between SLOE groupings and odds ratios (OR) were calculated. Results: A total of 2, 017 SLOEs from 781 US allopathic applicants were analyzed during the study period. Of the total, 277 (35%) applicants in our sample had any lower-third GA ranking, which significantly decreased an applicant's odds of matching in EM by 79% (OR 0.21, 95% CI, 0.12-0.34). Having more than one lower-third GA ranking did not further statistically decrease the odds of a successful EM match (OR 0.60, 95% CI 0.31-1.17). As a secondary finding of the study, results demonstrate that those applicants having no lower-third GA rankings had a nearly 5 times increased odds of an EM match (OR 4.84, 95% CI, 2.91-8.03). Conclusion: Having any lower-third GA ranking significantly reduced an applicant's chances of matching into an EM program. Faculty advisors should be aware of the increased risk of not matching for any applicant with any lower-third GA ranking and advise students appropriately, while maintaining the integrity of the SLOE and not divulging the confidential information contained within.